Peningkatan Hasil Belajar Mata Kuliah Teori Ekonomi Makro Dengan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) - Stefanus Hubertus Gusti Ma (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
This study aims to determine: (1) The implementation of cooperative learning model TPS learning Macroeconomic Theory. (2) Results of applied learning with cooperative learning model TPS. Classroom action research data collection techniques: (1) observation; (2) interview; (3) Documentation; (4) evaluation test. Data were analyzed by using the model of Jhon Elliot (Yuliawati, et al 2012:26). Based on the result of a classroom action research conducted two cycles showed that: the results of the pre-test measure of 30 student who complete 40% and did not complete 60% and continued with the result the first cycle of the 30 people who complete 63% and did not complete 37%. In the second cycle test result of 30 people with a significant increase of 100% completeness.